The needs of Pacific families affected by age-related cognitive impairment in New Zealand: interviews with providers from health-care organisations - Leigh Hale; Talai Mapusua; Pauline Norris; Rosalina Richards; Vanda Symon (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONPacific populations in New Zealand are aging, but little is known in the health-care environment about their experiences with cognitive impairment. AIMThe aim was to explore the needs of Pacific peoples affected by age-related cognitive decline from the perspectives of health-care providers. METHODSSix health-care service providers from organisations focused on Pacific patients were interviewed to determine services available to aged Pacific peoples, access, and whether they met Pacific people's needs. RESULTSThree areas of concern were identified by all participants: access to services; getting a diagnosis; and communication and language. Many experienced a lack of information and poor access to services. Diagnosis of cognitive impairment was frequently made difficult by inconsistent access to general practitioners in lower socio-economic areas. Communication was hindered by poor access to information in Pacific languages. DISCUSSIONCommon themes noted by all participating health-care providers indicated the needs of aged Pacific people experiencing cognitive decline were often not being met.